SUSTAINABLE HEALTHCARE MANAGEMENT AND E-HEALTH: PERCEPTIONS ABOUT PROBLEMS AND PROSPECTS. - Ghulam Muhammad Kundi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This paper was aimed to find the effect of E-Health on prospects and problems of E-health. A survey approach was used and a total of 169 respondents participated in the study. A closed-ended questionnaire was distributed among the respondents. Descriptive statistics and inferential statistics were used for testing hypotheses. SPSS 25 and AMOS-SEM software were used for analysis. For reliability and validity Cronbach alpha, EFA and CFA were run on data. To test the hypotheses, correlation and regression analysis in SPSS, and measurement model and structural model were tested in the AMOS-SEM. The study finds a significant relationship between e-health and prospects of e-health while negative but significant relationship between e-health and problems of e-health were reported. This study found that that underdeveloped countries and developing countries both should adopt E-health to reduce problems and increase the efficiency of healthcare institutions.